1988
DOI: 10.1037/0022-3514.54.5.847
|View full text |Cite
|
Sign up to set email alerts
|

Personal vulnerability, life events, and depressive symptoms: A test of a specific interactional model.

Abstract: We tested Beck's (1983) hypothesis that depressive symptoms occur when an individual experiences a negative life event that specifically matches the individual's personal motivational vulnerability. Ninety-eight undergraduates completed measures of depression level, recent life events, and sociotropic and autonomous achievement motivations. Consistent with the theory, sociotropy was associated with depression level and also served as a moderator of the relations between depression and frequency of recent negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
3
4

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(157 citation statements)
references
References 47 publications
(32 reference statements)
12
138
3
4
Order By: Relevance
“…People with sociotropic tendencies catastrophize the possibility of losing connection with others and are fearful of being excluded from their group (Blatt & Zuroff, 1992;Robins & Block, 1988). This may be consistent with individuals who have interdependent selfconstrual, emphasizing group harmony and defining themselves by their relationship with others.…”
Section: Eh Individualsmentioning
confidence: 63%
“…People with sociotropic tendencies catastrophize the possibility of losing connection with others and are fearful of being excluded from their group (Blatt & Zuroff, 1992;Robins & Block, 1988). This may be consistent with individuals who have interdependent selfconstrual, emphasizing group harmony and defining themselves by their relationship with others.…”
Section: Eh Individualsmentioning
confidence: 63%
“…[74][75][76][77] It has been suggested that stressful events or failure experiences are associated with depressive illness. [78][79][80] Such an outcome may stem from the stressor experience provoking the formation of attributions, which give rise to negative expectancies of future performance and may result in the development of cognitive disturbances, such as helplessness. 81,82 Alternatively, stressor experiences may give rise to neurochemical alterations that favor depressed mood.…”
Section: Biological Aspects Of Dysthymiamentioning
confidence: 99%
“…The interaction of sociotropic personality style and interpersonal-related events and interaction of autonomous personality style and achievement events would be associated with depressive symptoms. While previous studies found a weak (Bagby et al, 2001;Bieling & Alden, 2001) or even a lack of (Alford & Gerrity, 1995;Robins & Block, 1988;Segal, Shaw, Vella, & Katz, 1992) Sato and McCann (1998), it was hypothesized that the association from autonomous personality style and achievement-related events to depressive symptoms would be significant.…”
Section: Hypothesesmentioning
confidence: 95%
“…As sociotropy and autonomy are viewed as vulnerabilities (Sutton et al, 2011), stressful life events are necessary to trigger the development of depressive symptoms (Beck, 1983). Multiple studies found a significant interaction between the sociotropic personality style and negative social events to trigger depressive symptoms (Hammen et al, 1989;Mongrain & Blackburn, 2005;Nietzel & Harris, 1990;Robins & Block, 1988). Positive relationships were also found between sociotropy and depressive symptoms (Alford & Gerrity, 1995;Bagby et al, 2001;Bieling & Alden, 2001;Mazure, Raghavan, Maciejewski, Jacobs, & Bruce, 2001;Nelson, Hammen, Daley, Burge, & Davila, 2001;Sato & McCann, 1998;Sutton et al, 2011).…”
Section: Personality Styles As Vulnerabilities To Depressive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation